The resilience and wellbeing of public sector leaders. Issue 3 (13th August 2018) - Gray, Dee; Jones, Katherine
Abstract : Purpose: Wellbeing at work inspires global interest (WHO, 1997, 2010) which shapes international wellbeing whilst ensuring national wellbeing initiatives are devolved. This study is set in Wales, UK; the findings, however, are of interest to the global community as they present ways in which health promotion practices that are essentially salutogenic in nature (Antonovsky, 1987 ;Mittlemark and Bauer, 2017 ), may be operationalised through leadership development. The study is contextualised during a time of perceived public service overwhelm, and the purpose of this paper is to explore how a salutogenic model (Gray, 2017) captures a leadership narrative shaped by workplace stress, informing what the authors know about the resilience and wellbeing of leaders. Design/methodology/approach: The salutogenic model used in this exploratory study is based on the theories of Antonovsky (1979, 1987), and the conceptual work of De la Vega (2009). Participants were invited to take part in qualitative conversations, designed to explore leadership from a sense of coherence (SoC) perspective, and identify resilience and wellbeing descriptors across sectors. The data represented the lived experience of leader's resilience and wellbeing within their work role. A purposeful sample of leaders ( N =356) were invited to take part in the project, others were suggested as part of a snowball sampling approach ( N =36). The overall participant numbers were N =68. Findings: Using the SoC framework to explore resilience and wellbeing in terms of leadership, enabled participants to make sense of a stressful workplace environment, and share experiential knowledge that contributes to leadership development. The narrative that emerges is one in which leaders are feeling overwhelmed, and the broader influences of BREXIT, workforce and service user demographics, and organisational change are challenges to sustaining resilience. Participants suggest that leaders need to develop self-knowledge/awareness first, and role model the "resilient and well leader" to others. Research limitations/implications: The limitations of this study relate to the fact that given the potential for participation was nearer 400 leaders, the N =68 participants could not be deemed large enough to generalise the findings. However, this was a scoping study exercise, designed to explore resilience and wellbeing through SoC conversations and to surface descriptors that would add to what the authors know about contemporary leadership. The study could be improved in the future by the collection of more descriptors, and where practical segmentation of descriptors may provide further insight in terms of comparison between professions/sectors. Practical implications: The authors know that leadership is linked to positive and negative outcomes for employees; it is, therefore, prudent to consider how the authors can support both current and future leaders, to incorporate their own and others' resilience and wellbeing into their leadership repertoire. This may well be best facilitated through health leadership which is known to have a positive association in determining the psychological climate of the workplace. Leadership authenticity means leaders should be able to ask for help, if leaders are struggling with that, then the authors need to examine leadership from a cultural perspective. In practical terms, the generalised resistance resources (GRRs) put forward by the participants may also form local as well as national wellbeing action plans for the future. Social implications: Leadership is socially constructed within the organisational context, and the resilience and wellbeing of leaders is affected by the organisational health determinants in the working environment. If the authors are to consider how leaders are to develop an SoC for themselves and others, the authors need to attend to how the leader learns in the context. This is because their SoC is also shaped by the challenges they experience, and socio-constructed learning becomes neurologically embedded, so that ways of thinking, feeling and behaving are reinforced and exhibited over and over again. Originality/value: This exploratory study demonstrates the efficacy of the salutogenic model to stimulate dialogue about a potentially sensitive subject. Many of the answers rest with the leaders themselves. The authors held conversations with leaders from the public services in Wales, identified "best self" and "peripheral" variables that leaders manifest across the various organisations they lead, and leaders produced a range of GRRs to support resilience and wellbeing across sectors in the future. There is a growing recognition that in terms of health leadership capability, there will be a premium on knowledge capital that pertains to improving the resilience and wellbeing of employees.